Air velocity modeling velocity of the air around the trunk road train with installed rolling roof fairings - Nesterenko, Mykola; Skoryk, Maksum; Shapoval, Mykola; Nesterenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2019)
The new rolling roof fairing installed in the tractor non-bonnet cab main train layout constructing are given. After analyzing existing exhausting elements installed on the tractor highway trailer and a large number of roof rails, it has been substantiated the expediency of installing a movable rope on the tractor roof, which can change the angle of the trailer airflow link with the combination of two movements - vertical and horizontal. The combination of these movements enables to change the parameters of streamline. For this purpose, the basic hydraulic control scheme is designed, which has a number of advantages: the starting units movements smoothness, the ability to continuously adjust the speed in a wide range, low inertia, simplicity of management and automation, high operational reliability and resistance to overload. Due to the modern capabilities and development of sophisticated electronic control systems through the introduction of such a system in the control process of hydraulic cylinders can ensure the system reliability, efficiency, ergonomics and safety equipment.